Harmonisasi dan Disparitas : Pembagian Warisan bagi Anak Adopsi dalam Hukum Perdata dan Hukum Adat Karo - Nia Anjunita Sari Purba; Sri Hadiningrum; Parlaungan G Siahaan; Anggun Adelita; Andina Larasati; Enjelita Dwi Maharani (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2025)
This study is entitled Harmonization and Disparity: Comparative Analysis of the Division of Inheritance for Adopted Children According to Civil Law and Karo Customary Law. The main focus of this study is to identify and analyze the differences and common ground between the national legal system in this case civil law and Karo customary law in determining inheritance rights for adopted children. In civil law, adopted children are legally recognized as having equal standing with biological children. This provision strengthens the rights of adopted children to receive inheritance from their adoptive parents. On the other hand, in the context of Karo customary law, recognition of adopted children as heirs is still limited. Generally, only male adopted children are given inheritance rights to searched property, while inheritance remains inherited by male descendants from the bloodline. The problems studied in this proposal include how the law treats adopted children in the division of inheritance according to the two legal systems, the challenges faced in realizing the inheritance rights of adopted children, and how to formulate efforts to harmonize civil law and customary law in order to create equal justice. This study uses a qualitative approach with a library research type. The results of the study indicate that there is a fundamental disparity between civil law and Karo customary law in granting inheritance rights to adopted children. Civil law stipulates that adopted children who are legally adopted through the courts have equal rights to biological children, including the right to legitieme portie. Thus, a more inclusive, adaptive legal system can be created that guarantees justice for all children without discrimination based on birth status or gender.